Dermatoses in Himalayas: Pattern of Skin Diseases in Himalayan Region of Nepal - Poudyal, A.K.; Paudel, U.; Khadka, R.; Sharma, S.; Pokhrel, K; Das, A.K.; Parajuli, S. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Background: Skin diseases are the major cause of out-patient visit in Nepal. Department of Health Services, Nepal ranks skin diseases as fourth common cause of out-patient visit throughout the country. The objective of the study was to determine the pattern of different skin diseases in Himalayan region of Nepal. Material and methods: A cross sectional descriptive study design was conducted in a health camp setting in which 148 community people visited the camp with dermatological diseases. Information about socio-demographic and dermatological diseases were collected with a structured performa. Results: The most common primary diagnosis was pigmentary anomaly (20.3%) followed by Eczemas (18.9%), Superficial mycoses (10.8%), and acne (10.1%). In all skin diseases male were more affected as compared to female. Conclusions: The dermatoses of Himalayan region are pigmentary anomalies being most common, followed by eczemas, superficial mycoses, acne, photodermatoses, scabies, urticaria, benign tumours and pyodermas. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.25-28